MEDICO-SOCIAL AND INDIVIDUAL PSYCHOLOGICAL CHARACTERISTICS OF DRUG ADDICTED TEENAGERS AND THEIR HEALTHY RELATIVES - Z. A. Khusnutdinova (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
We conducted the research for detection of premorbid medico-social and personal features of related teenagers, using and not using psychoactive agents. Comparative analysis of 90 teenagers with drug addiction and their 90 healthy relatives (control group) was realized. Research was conducted by the method of anonymous questioning with use of specially developed questionnaire consisting of 88 questions, and also psychological methods -16 personal factors Kettell test, SMIL, and Zung depression test. Dispersive analysis was used to determine factors of medico-social character which can be considered informative for diagnostics of addiction deviations. Method of experimental psychology allowed to reveal individual and psychological features of teenagers leading to formation of addictive behavior. Teenagers suffering from drug addiction are much less socially successful than their healthy relatives. As compared to their healthy relatives, drug addicts' anamneses had more medico-social and premorbid factors of addictive risk: various neurotic episodes during childhood, craniocereberal traumas. They were exposed to actions of sexual violence more often. Their typical characteristics include tendency to internal aggression, parasuicide thoughts, suicide attempts and a paracriminal circle of contacts. Results of research at this stage gave the grounds to assume that under identical family conditions of education some teenagers are getting drug addiction, while others don't. This can be explained by the existence of individual and personal features which can already be induced by factors outside of the family. Experimental and psychological method revealed the individual and psychological features of teenagers promoting formation of dependent behavior. Unlike their healthy relatives teenage addicts have peculiar features such as aggressive tendencies, explosive nature of reaction, uneasiness and nervousness reflecting a condition of the extreme stress, hyper compensatory involvement of various protective mechanisms, hyperactivity in their search of an exit to their difficult situation, lower background of mood and narrow zone of contacts. Thus, in comparison with healthy relatives, anamnesis of teenagers addicts more often contain medico-social, behavioral and premorbid predictors of addictive behavior, and a number of specific features. All this needs to be considered while setting up individual programs of rehabilitation, and during development of primary prevention programs of psychoactive substances use in the youth environment.